Marketing Communication Strategy of Warung Sate Lego In the Perspective of Islam - Nur Rochman Syah; M Rifa'i (Sahafa Journal of Islamic Communication, 2018)
AbstractThe development of technology in an increasingly modern era with the presence of smartphone allows businesses to sell their goods online, not only through the web, but also through social networks such as facebook, twitter and instagram. This research explains communication marketing strategy of satay lego food stall implemented with Islamic marketing system using social media facebook and instagram. Warung satay lego is a typical Ponorogo food culinary business that has been running for about three years. It is using facebook and instagram as an online marketing communication media to promote their product. This research uses qualitative descriptive method by collecting data through interview, observation and documentation. The informants in this study are the owner or manager of Warung Sate Lego and social media advertisement of sate lego stall. The theory used is the theory of marketing communication mix in the promotion that is through advertising, sales promotion, public relations, direct sales and internet marketing. The result of this research is that the marketing communication strategy done in Warung Sate Lego used Islam perspective. Marketing method used is marketing communication mix with promotion implemented through social media, facebook, instagram, whatsapp and also website. From the strategy used, there is an increase in purchases which is in accordance with the purpose of marketing communications run by Warung Sate Lego.Keywords: Islamic marketing communication strategy, Promotion, Facebook and Instagram